2007
DOI: 10.1207/s15327663jcp1701_5
|View full text |Cite
|
Sign up to set email alerts
|

Regret and Behavior: Comment on Zeelenberg and Pieters

Abstract: Zeelenberg and Pieter's (2007) regret regulation theory 1.0 offers a synthesis that brings together concepts spanning numerous literatures. We have no substantive disagreement with their theory, but instead offer 3 observations to further aid regret researchers studying consumer decision making. First, the overall arch of any regret theory must be situated within an understanding of behavior regulation. Second, the distinction between regrets of action versus inaction is best understood in terms of motivationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 31 publications
(23 reference statements)
2
39
0
3
Order By: Relevance
“…Respondents may have utilized defense mechanisms; it may be psychologically easier for people to report their regret feelings for inaction than action or than, for example, hedonic consumption. Alternatively, it can be suggested that respondents did indeed feel more guilt over indulging themselves in hedonic consumption, losing self-control and promotion failures (Roese et al 2007) than over the purchase of utilitarian products associated with a perception of lower consumer value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents may have utilized defense mechanisms; it may be psychologically easier for people to report their regret feelings for inaction than action or than, for example, hedonic consumption. Alternatively, it can be suggested that respondents did indeed feel more guilt over indulging themselves in hedonic consumption, losing self-control and promotion failures (Roese et al 2007) than over the purchase of utilitarian products associated with a perception of lower consumer value.…”
Section: Resultsmentioning
confidence: 99%
“…This can equally stem from decisions to act or from decisions not to act Zeelenberg 2007, Roese et al 2007). Roese et al (2007) argue that regrets of action and inaction are different in terms of their motivational implications; regrets of action tend to center on avoidance and are related to prevention failures (e.g., not being able to avoid an undesirable product or situation), whereas regrets of inaction tend to center on approach and are related to promotion failures (e.g., not being able to approach a desired product or situation). Regret for the purchase of utilitarian products occurs associated with a perception of value, while regret of purchase of hedonic products cause guilt feeling associated with a perception of transgression, selfindulgence and self-control failure (Miao 2011).…”
Section: The Constructs Of Consumer Guiltmentioning
confidence: 98%
“…Regrets of inaction are found to be more likely to be activated when the individual has suffered a promotion failure, as suggested by Roese et al (2007). As explained by one informant, talking about his collage:…”
Section: Regret Of Action and Inactionmentioning
confidence: 85%
“…They manage stressful emotional experiences in purchase-related situations by means of problem-focused coping and emotion-focused coping strategies In problem-focused coping, consumer tries to manage the source of a negative emotional experience and act on the threat to reduce or avoid it; in emotion-focused coping, consumer tries to manage the emotions experienced as a result of a stressful situation by changing the meaning of the event or regulating the expression of the emotion (Yi and Baumgartner 2004). They are also labeled as behavioral and cognitive coping (Roese et al 2007). …”
Section: Coping With Consumer Guiltmentioning
confidence: 99%
“…As Roese, Summerville and Fessel (2007) have pointed out, this leads to problems of circularity, in that researchers produce findings that support their definitions, but which do not necessarily reflect the reality of the phenomenon being studied. One way around this might be the inclusion of more discriminating definitions and measures of regret, such as the psychometric and phenomenological instruments used in emotion research.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%